An open Monte Carlo based implementation of Gauss's method for initial orbit determination - José B. Batista-Mendoza; Eduardo Chung; Adam’s Martínez-Soto; Joaquín Fábrega-Polleri; Carlos A. Fernández-Valdés (Tecnociencia)
Hundreds or thousands of Near-Earth Asteroids (NEAs) are discovered every year, so being able to determine their orbits to follow them successfully in the future is essential to warn of the danger they could present. Numerous methods have been developed to improve the precision and efficiency of calculations used in the Initial Orbit Determination (IOD), with Gauss’s method being the benchmark due to its intuitive formulation, comparable precision, and historical importance. Herein, we present the results of the development of a new